IMPROVE ENGLISH VOCABULARY USING FLASHCARDS - Agis Elfira Agis Elfira; Cici Situmorang; Glenndiaz Nazriel Nugraha; Amanda Wulandari (Journal of Innovative and Creativity, 2026)
Vocabulary has a very important role in learning English, but many students still have difficulty remembering and using vocabulary because of the monotonous and uninteresting learning medium. This study aims to explain how the use of Flashcards media through the Flashcards Time Challenge game in improving English vocabulary mastery. This study uses a qualitative method with a descriptive approach. The subject in this study is a student of the Cirebon Prima Bangsa Institute. Observation and interviews were used as data collection techniques. The results of the study show that the use of Flashcards media is able to increase students' enthusiasm, activeness, and motivation in learning vocabulary. Basic vocabulary such as nouns are easier for students to understand and remember because the learning is in the form of visual media combined with game activities. Thus, learning using Flashcards media through the Time Challenge game can be used as an effective and fun English vocabulary learning strategy.